Emergency notification system (MENA Report, 2015)
A. General Description 1. This Emergency Notification System shall provide a robust, interactive, reliable, high-speed notification system thajt can send notifications to hundreds of thousands of recipients and allow for the recipient to be able to select options for additional information or clarification. 2.